Bioinformatics analysis identifies heparan sulfate proteoglycans acting as different progress subtypes of biliary atresia - Ding, Zequan; Song, Wenyu; Zhu, Wei; Xie, Hua; Zhu, Zhongxian; Tang, Weibing (Frontiers in Pediatrics, 2023)
Background Biliary atresia (BA) is a life-threatening disorder, which is characterized by the obliteration of biliary tracts. Heparan sulfate proteoglycans (HSPGs) are important regulators in liver diseases. Whether HSPGs participate in the development of BA is poorly understood. Methods RNA-seq dataset GSE122340, including 171 BA and 7 normal liver tissue, was integrated for bioinformatic analysis. R function “wilcox.test” was used to compare HSPGs expression levels, and “cor.test” was used to evaluate the correlation analysis. MCPcounter was used to assess the abundance of immunocytes. Molecular subtypes of BA were clustered via NMF clustering and LASSO regression was applied to screen hub HSPGs genes in BA clusters. RT-PCR analysis was used to assess the expression of hub HSPGs in BA liver. Immunohistochemical staining and immunofluorescence assay were used to evaluated the location and expression of hub HSPGs in BA liver tissue. Results Majority of HSPGs was up-regulated in BA and correlated with liver fibrosis and ductular reaction markers. The abundance of immunocytes was higher in BA and associated with HSPGs. Based on the expression of HSPGs, BA patients were classified into 3 subtypes (C1, C2, and C3). Pathway enrichment analysis revealed C1 subtype had severe liver injury with SDC4 identified as the hub gene, while C3 subtype presented relatively normal liver condition with GPC3 identified as the hub gene. RT-PCR analysis demonstrated the expression levels of 2 hub genes in BA liver tissue with different jaundice clearance standards. Immunohistochemical staining and immunofluorescence assay showed that SDC4 was mostly expressed in ductular reaction area, while GPC3 was mostly expressed in hepatocytes. Conclusion Majority of HSPGs are aberrant expressed in BA. The subtype hub gene SDC4 and GPC3 might be used as a potential indicator for different types of prognosis.